2001
DOI: 10.1097/00000542-200107000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Five Experimental Pain Tests to Measure Analgesic Effects of Alfentanil

Abstract: Electrical, pressure, and ice-water pain, but not ischemic and heat pain, provide significant concentration-response curves in the clinically relevant range of 200 ng/ml alfentanil or lower. The power to detect a clinically relevant shift of the curve is similar in the three tests. The appropriate test(s) for pharmacodynamic studies should be chosen according to the investigated drug(s) and the study design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 0 publications
3
47
0
Order By: Relevance
“…However it has been shown that in experimental models with a high reproducibility sample sizes below 10 are powered to show the effect of analgesics [7]. Accordingly we found a well designed study with a sample size of seven, and this was the minimum sample size for the studies included in this review [8].…”
Section: Methodsmentioning
confidence: 90%
See 4 more Smart Citations
“…However it has been shown that in experimental models with a high reproducibility sample sizes below 10 are powered to show the effect of analgesics [7]. Accordingly we found a well designed study with a sample size of seven, and this was the minimum sample size for the studies included in this review [8].…”
Section: Methodsmentioning
confidence: 90%
“…In the study by Black et al both pain intensity and the affective component 'bothersomeness' was scored and alfentanil reduced both parameters [8,52].…”
Section: Figurementioning
confidence: 97%
See 3 more Smart Citations